THE EFFECT OF FIRM SIZE, LEVERAGE, AND LIQUIDITY ON COMPANY VALUE - Yulianson, Willy; Hastuti, Rini Tri (Graduate Program of Universitas Tarumanagara, 2024)
Firm value can also be influenced by the company's ability to meet its short-term obligations or often referred to as liquidity. A company that has good liquidity will be considered by investors and creditors as having good performance. So that investors have an interest in investing in the company. This study aims to show the influence of firm size, leverage and liquidity partially on firm value. This study uses a sample of company data listed on the Indonesia Stock Exchange (IDX) for 2019-2021. The sampling method used is purposive sampling method and the samples used are 26 companies. the sample used was 78 data which was processed and analysed using eviews 12 (econometrics views). but it does not have a significant effect, while the firm size variable has a negative relationship to firm value but has a significant effect.